Composition of gas produced from the direct combustion and pyrolysis of biomass; Process Safety and Environmental Protection; Vol. 156 - Glushkov D. O. Dmitry Olegovich; Nyashina G. S. Galina Sergeevna; Anand R.; Strizhak P. A. Pavel Alexandrovich (2021, 2021)
Title screen